Immuno-Modulatory Effect Of Makaradhwaja - Dhundi, Shraddha (International Journal of Pharmaceutical & Biological Archive, 2011)
The term immune-modulation is used for describing the effect of various chemical mediators, hormones and drugs on the immune system. The human body has the ability to resist almost all types of organism or toxins that tend to damage the tissue and organ. This capability is called immunity. Makaradhwaja is a metalo-mineral preparation, which is most popular and effective in Kupipakwa preparation of Ayurvedic medicine which is mainly used for Rasayana purposes. In this study total 18 Swiss albino mice of either sex weighing between 20 - 36 g were divided into three groups, each having 3 males and 3 females. Sample of Makaradhwaja was taken and few drops of 5% gum acacia suspension were added, it was further grounded for 5 minutes and the volume was made up with distilled water, suspension form in 5% gum acacia orally with the help of plastic tube attached to a tuberculin syringe. Makaradhwaja comes to 16.25 mg kg-1 and was rounded of to 16 mg kg-1 dose, for 10 consecutive days. Study suggested that the test drug has significant CMI (cell mediated immunity) enhancing effect but has no significant effect on humoral anti-body formation.